Progress in fish gastrointestinal microbiota research - An R. Wang; Chao Ran; Einar Ringø; Zhi G. Zhou (Reviews in Aquaculture, 2018)
The gastrointestinal (GI) microbiota of vertebrates plays critical roles in nutrition, development, immunity and resistance against invasive pathogens. In the past decade, research of the GI microbiota of mammals has drastically increased our knowledge on the microbiota and their relationship with health and disease. However, our understanding of fish intestinal microbiota is limited. This review provides an overview of research on fish gut microbiota, including microbial composition, formation, factors that affect the GI microbes and characteristics of fish intestinal microbiota compared with human and mice. Further, the updated research on gnotobiotic zebrafish is elaborated and the insights gained on functions of the fish intestinal microbiota are discussed. Understanding the intestinal microbiota of fish will guide the development of probiotics, prebiotics and hopefully probiotic effectors as novel additives to improve the health of fish.